Ser, estar e ficar em construções com adjetivos e particípios - Rebouças, Rute Alexandra Félix (elingUP: Revista Eletrónica de Linguística dos Estudantes da Universidade do Porto, 2018)
Portuguese language, Unlike many others, has the distinction between ser and estar and has a verb often used in resultative constructions (ficar). The constructions with these verbs, ser, estar and ficar + adjective and/or past participle, have been studied for a long time, since, as they present similarities and dissimilarities between them. With the objective of finding regularities in the selection of these verbs combined with adjectives and also with past participles, we collected a corpus (from CETEMpúblico) and, subsequently, analyzed samples based on the theoretical framework.